التغيرات المناخية وآثارها الضارة وكيفيات معالجتها - مقدم, م; زحوف, نجية (جامعة الوادي University of Eloued, 2019)
الملخص باللغة العربية يحذر خبراء علم المناخ من ارتفاع متوسط درجة حرارة الغلاف الجوي والمحيطات، بفعل التركيزات المتراكمة للغازات الدفيئة الحالية و المستقبلية في الغلاف الجوي، و النشطات البشرية المتنامية منذ النصف الثاني من القرن العشرين. وإعتبارا للوتيرة الحالية المتصاعدة، يعتقد العلماء أن متوسط درجة حرارة سطح الكرة الارضية سوف يصل إلى مستوى لا تحمد عقباه مع نهاية القرن الواحد و العشرين تنجم عنه انعكاسات ضارة تؤثر سلبا على النظم البيئية و التجمعات البشرية، ولاسيما ارتفاع مستوى البحار والمحيطات وظهور أحداث متطرفة، كالجفاف والفيضانات وانتشار الآفات والأمراض المعدية والوبائية و تراجع منسوب المياه الصالحة والمحصول الزراعي الأساسي كالقمح والذرة. و في هذا الاتجاه يعمل المجتمع الدولي منذ عقود من خلال المؤتمرات و الاتفاقيات على مضاعفة المجهود لاحتواء درجة الحرارة عند مستوى يحول دون الحاق الضرر بالنظام المناخي و تجنب الانعكاسات الضارة المحتملة، بالامتثال لالتزامات خفض انبعاث غازات الدفيئة و تعزيز القدرة على التكيف بإدخال تعديل على النظم البيئية للحد من الآثار السلبية. الكلمات المفتاحية: التغيرات المناخية، النظم البيئية، الغازات الدفيئة، التخفيض، التكيف. الملخص باللغة الانجليزيةClimatologists warn of the danger of rising average temperatures in the atmosphere and oceans due to current and future concentrations of greenhouse gases accumulated in the atmosphere, as a result of increased activity.Since the second half of the 20th century.That is why the average temperature on the surface of the Earth will reach a record level by the end of the 21st century. This will result in adverse effects on ecosystems and human populations, including: rising sea and ocean levels, the occurrence of extreme events such as droughts, floods, the spread of infectious and epidemiological diseases, falling water levels and basic agricultural production wheat and corn etc.. ... For that reason, the international community has been striving for decades, through conferences and climate conventions, to redouble efforts to maintain the temperature at a level that avoids damage to the climate system and avoid possible adverse effects by complying with commitments to reduce greenhouse gas emissions and by strengthening adaptation to the adverse effects of climate change. Keywords: rising average temperatures, ecosystems, to reduce, greenhouse gas emissions, adaptation.
Keywords: لتغيرات المناخية ; النظم البيئية، ; الغازات الدفيئة، ; لتخفيض ; التكيف; rising average temperatures ; ecosystems ; to reduce, ; greenhouse gas emissions, ; adaptation.